The Quest for the Most Suitable Density Profile of the Bubble Nuclei - Yadav, Purujeet (My University, 2023)
In the centre of a bubble nucleus, the neutron and proton density is lower. Consequently, both the mass and charge density profiles exhibit a central depression. Complex and laborious numerical methods are utilised to disclose the profile of the bubble nucleus. Currently, numerous mathematical profiles feature a central decline. This thesis investigates the prospect of a correlation between mathematical profiles and the density profile of bubble nuclei. Considered are ten distinct categories of mathematical profiles. Bimodal skew-symmetric normal distribution emerged as the optimal profile, while Cosh-Gaussian performed well in instances where the bubble structure was more pronounced. A comprehensive and comparative report is provided.
Keywords: Bubble Nuclei; Nuclear Density; Cosh-Gaussian Profile; Biomodal skew symmetric normal; Distribution; Bell shaped curves